The Changing Shape of Work
X, 226 p.
Keywords: The contributors provide critical accounts of the transformation of work and employment during the final quarter of the twentieth century. They draw on their own and others' current research to identify the origins and consequences of these developments and illustrate their impact on society, organizations, individuals and communities. Wide-ranging reviews of changes in labour markets and employment practices provide the context for detailed studies, including the 'feminization' of work, informal working, responses to unemployment, organizational culture, and Total Quality Management.